HUBUNGAN PENGETAHUAN GIZI, KONSUMSI ZAT BESI, VITAMIN C DAN TABLET TAMBAH DARAH DENGAN STATUS ANEMIA PADA SISWI SMAN 1 UBUD, GIANYAR - desynta runkat; I Made Rodja Suantara; Ida Ayu Eka Padmiari (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2019)
Anemia is a condition with lower blood hemoglobin levels than normal caused by iron deficiency. The purpose of this study is to determine the relationship between nutrition knowledge, consumption of iron, vitamin C and iron tablet with anemia status in female students of SMAN 1 Ubud, Gianyar. This research used observational with a cross sectional design. The samples in this study were 77 female students. Anemia status data was obtained from hemoglobin examination using the Hb meter method, consumption data measured by food recall 2 x 24 hours and nutrition knowledge used interview method with questionnaire. Data was analyzed using chi square. The results of the study 6 samples (7,8%) were anemic, 75 samples (97,4%) had consumption of iron in the category of deficits, 63 samples (81,8%) had consumption of vitamin C in the category of deficits, 64 samples (83,1%) did not take vitamin C supplements, 64 students (83,1%) did not take iron supplements, 72 samples (93.5%) did not take iron tablets and 50 samples (64,9%) had knowledge of nutrition in sufficient categories. There was a relationship between nutrition knowledge with consumption of iron and vitamin C (P 0.05). Keywords : nutrition knowledge, iron, vitamin C, iron tablet, anemia statusPol